Precambrian tectonic inheritance control of the NE Brazilian continental margin revealed by Curie point depth estimation - Cruz Oliveira, Jefferson Tavares; Barbosa, José Antonio; de Castro, David; Correia, Paulo; Magalhães, José Ricardo; Correia Filho, Osvaldo; Buarque, Bruno (Annals of geophysics, 2021)
An investigation of Curie point depths (CPD) based on spectral analysis of airborne magnetic data was carried out in the NE Brazilian continental margin. The studied region represents a narrow hyper-extended margin with three sedimentary basins. Regional geothermal gradient and heat flow were also calculated. CPD results were integrated with interpretation of 2D deep seismic data and with estimated isostatic Moho depths. The results reveal that the narrow hyper-extended crust is 150 km wide in the southern sector and 80 km wide in the north, with a narrow ocean-continental transition (OCT) zone that varies from 50 km wide in the south sector to 30 to 20 km wide in the north. The CPD isotherm showed the strong influence of the three main continental blocks of Borborema ́s Shield in the tectonic evolution of the three marginal basins. The CPD analysis corroborated models provided by gravimetric data and successfully demonstrated the sharp control of basement compartments on the thermal properties of the marginal basins domains